Is surgical ligation of patent ductus arteriosus necessary? The Western Australian experience of conservative management. Issue 3 (21st April 2005) - Brooks, J M; Travadi, J N; Patole, S K; Doherty, D A; Simmer, K
Abstract : Background: Surgical ligation of patent ductus arteriosus (PDA) is widely practised in preterm infants despite no clear evidence that this improves outcomes. Geographical isolation meant that ductal ligation was not an option in King Edward Memorial Hospital until recently. Objective: A retrospective data analysis to test the hypothesis that outcomes of infants with persistent PDA were no worse than those of infants with no significant duct or a duct that closed after medical treatment. Patients and Methods: A total of 252 infants (gestation ⩽28 weeks) born between 1 January 2000 and 30 June 2002 were divided into three groups: group 1, no significant PDA (n  =  154); group 2, significant PDA which closed after medical treatment (n  =  65); group 3, significant PDA remaining patent after medical treatment (n  =  33). A significant PDA was defined by a left atrium to aortic root ratio of >1.4 or a ductal diameter >1.5 mm with a left to right shunt. Results: Twenty four (10%) infants died at median (interquartile range) 15.5 (9–35) days. After adjustment for gestational age, relative to group 1, the infants from group 3 were at a 4.02 times increased risk of death (95% confidence interval 1.12 to 14.51). There was no significant difference between groups in the incidence of chronic lung disease, chronic lung disease or death, necrotising enterocolitis, intraventricular haemorrhage, duration of oxygen, or hospital stay. Conclusion: Mortality was higher in infants with a persistent PDA, but other morbidities were not significantly different. A randomised trial is needed to determine whether surgical ligation will reduce mortality in such infants.